2000
DOI: 10.1159/000028109
|View full text |Cite
|
Sign up to set email alerts
|

Bronchus-Associated Lymphoid Tissue (BALT) Is Not Present in the Normal Adult Lung but in Different Diseases

Abstract: Bronchus-associated lymphoid tissue (BALT) was first described in the lungs of rabbits and differs greatly between species. It is part of the integrated mucosal immune system. This review clarifies its morphological definition and focuses on the situation in humans. The frequency of BALT at different ages, after chronic stimulation and in different diseases is described. In healthy humans, BALT can only be found in the lungs of children and adolescents. The role of BALT in lung transplantation and in the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
143
0
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(154 citation statements)
references
References 38 publications
4
143
0
4
Order By: Relevance
“…It is possible that the presumed existence of "constitutive BALT" has made lymphoid neogenesis in the lung less obvious. However, BALT has been demonstrated not to exist in normal human lungs (29). We also observed a significantly larger number of lymphoid tissues containing HEVs in BOS lungs than in normal control lungs (Fig.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…It is possible that the presumed existence of "constitutive BALT" has made lymphoid neogenesis in the lung less obvious. However, BALT has been demonstrated not to exist in normal human lungs (29). We also observed a significantly larger number of lymphoid tissues containing HEVs in BOS lungs than in normal control lungs (Fig.…”
Section: Discussionmentioning
confidence: 50%
“…Differences among species are another important limitation of an animal experiment, particularly in the organization of intrapulmonary lymphoid tissues such as BALT (29,47). Despite these limitations, we emphasize that the animal experiments in the present study complemented the limitations in the human study in many ways and provided important insights regarding the role of intrapulmonary de novo lymphoid tissue in OB after lung transplantation.…”
Section: Discussionmentioning
confidence: 78%
“…BALT have been described in the human fetus and infant lung (Gould and Isaacson, 1993). Although they disappear in the normal adult lung (Tschernig and Pabst, 2000), they develop in lung inflammatory diseases such as fibrosis, pneumonia, hypersensitivity pneumonitis, diffuse pan-bronchiolitis and in tobacco-induced inflammation. We found that Ti-BALT are adjacent to the tumor area in NSCLC, absent in the nontumoral tissue and their number is independent of the smoking history of the patients.…”
Section: Immune Infiltration In Human Tumorsmentioning
confidence: 99%
“…However, BALT is inducible in humans and mice after inflammation in the lung (40,45) (so-called iBALT). iBALT occurs in chronic lung infections in humans (53), as well as in mice with repeated virus infections of the lung (10). Mice lacking spleen, lymph nodes, and Peyer's patches develop extensive BALT in response to influenza challenge, clear influenza infection, and when BALT is present survive higher doses of the virus than do normal mice (32,47).…”
Section: Contact Dermatitis/viral Exanthemamentioning
confidence: 99%